2018
DOI: 10.3390/ijms19040995
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Type 1 Diabetes

Abstract: Recently, the onset of type 1 diabetes (T1D) has increased rapidly and became a major public health concern worldwide. Various factors are associated with the development of T1D, such as diet, genome, and intestinal microbiota. The gastrointestinal (GI) tract harbors a complex and dynamic population of microorganisms, the gut microbiota, which exert a marked influence on the host homeostasis and metabolic diseases. Recent evidence shows that altered gut bacterial composition (dysbiosis) is highly associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 84 publications
4
112
0
13
Order By: Relevance
“…Diabetes. Micobiome analysis has been performed in a few studies to elucidate the role of microbiota in driving the pathogenesis of diabetes mellitus [120][121][122]. In the context of fungal involvement, Soyucen and collaborators found that besides Echerichia coli, C. albicans and Enterobacteriaceae colonization were increased in the patients with type 1 diabetes mellitus (T1DM), whereas Bifidobacterium colonization was reduced [123].…”
Section: Inflammatory Bowel Syndromes (Ibs)mentioning
confidence: 99%
“…Diabetes. Micobiome analysis has been performed in a few studies to elucidate the role of microbiota in driving the pathogenesis of diabetes mellitus [120][121][122]. In the context of fungal involvement, Soyucen and collaborators found that besides Echerichia coli, C. albicans and Enterobacteriaceae colonization were increased in the patients with type 1 diabetes mellitus (T1DM), whereas Bifidobacterium colonization was reduced [123].…”
Section: Inflammatory Bowel Syndromes (Ibs)mentioning
confidence: 99%
“…In such acquired endocrinological diseases as obesity, type 2 diabetes (not related to heredity) can be attributed to pathological conditions due to metabolic disorders involving the microbiota. Microbiota can influence the development of diabetes [19]. Changes in the microbiological composition-dysbacteriosiscaused, for example, by the use of antibiotics, may contribute to an increase in insulin dysfunction, a long-term consequence of which is the development of type 2 diabetes.…”
Section: Microbiota Dysfunction In Pathology 31 Diseases Of the Digementioning
confidence: 99%
“…Studies from animals and humans have indicated that there is a marked difference in the gut microbiota between obese and lean subjects, and the microbiota in the obese may further manipulate host metabolism leading to enhanced adiposity, inflammatory response, oxidative stress, and metabolic dysfunction . Xu et al also indicated that melatonin improves the richness and diversity of gut microbiota and reverses 14 operational taxonomic units (OTUs) in HF diet‐fed mice, especially for the ratio of Firmicutes to Bacteroidetes .…”
Section: Introductionmentioning
confidence: 99%